(untitled) (Bioresearch Communications, 2024)
Background: Pregnancy induced hypertension (PIH) is one of the major complications of pregnancy. Inadequate calcium (Ca) intake is considered a public health problem in some vulnerable groups, especially pregnant women. A balanced diet during pregnancy with adequate Ca should be the ideal solution, and to proceed in this direction, evidence is required on the nature and extent of Ca deficiency in the diet of PIH mothers. Objectives: To assess the dietary intake of Ca in PIH (compared to non-PIH) mothers and to explore the factors affecting the intake of those nutrients. Methods: Under an observational case-control design, we recruited 300 Bangladeshi pregnant women in two groups (150 with and 150 without PIH), aged between 20-40 years (from 3 hospitals in Dhaka) at the 3rd trimester of pregnancy. A pre-tested questionnaire was used to collect the data. The first part of the questionnaire was allocated to general socio-demographic and clinical characteristics. Secondly, a food frequency questionnaire was used to estimate individual dietary Ca intake. Results: The dietary Calcium intake [(mg/day), median (range)] was significantly lower [265(111-487)] (p<0.001) in the PIH compared to the non-PIH [350(201-984) ;(p<0.001)] group. On bivariate analysis, the dietary Calcium intakes had a significantly negative correlation with mean blood pressure which was considered an indicator of the severity of PIH (r=-0.276; p<0.001) for Ca. On regression analysis, PIH was found to be significantly associated with a lower intake of Ca (b=-0.009; p<0.001) when the effects of age, family history of HTN and family income were adjusted. Conclusion: Dietary consumption of Calcium during pregnancy is much lower than those recommended in our population, PIH seems to have an association with dietary deficiency of Calcium in pregnant women. Bioresearch Commu. 10(2): 1612-1618, 2024 (July)